« D’homme à homme » : Récits de rencontres entre Yekkes et Arabes en Palestine/Israël (années 1930 et 1940) - Patrick Farges (Genre & Histoire)
While German-Jewish emigration to Mandate Palestine has attracted renewed interest over the last twenty years or so, not all of its aspects have received the same attention. Numerous studies have stressed the “great contribution” of German-speaking Jews to the construction of Israeli society, but little research has yet been conducted which places this migration in its Middle Eastern context. In view of the recent interest in the gendered aspects within German-Jewish history – including issues of masculinity – the time is ripe to focus on the interactions between German-Jewish immigrants (‘Yekkes’) and their Middle Eastern environment – especially their Arabic neighbours – before and after the war of 1948 and the “partition” of Palestine. This article, which is based on autobiographical accounts and oral history interviews conducted in the early 1990s, focuses on the narratives of man-to-man “close encounters” with the Arabs. The image of the masculinity of local Arabs appears ambivalent. The article shows that by confronting “Orientalistic” clichés with retrospective interpretative work, the narratives told by (male) Yekkes constructed “fluid” masculine identities which sought to assert their distinctiveness and to receive restrospective historical legitimation. In the process, they also negotiated a distinctive cultural habitus.